Tuberocephalus tsengi (Tao, 1963) STAT. REV. (Hemiptera: Aphididae), an East Asian Artemisia-feeding aphid species introduced to Britain - Blackman, Roger L.; Brightwell, Robert; Dransfield, Robert D.; Brown, Paul A. (Zootaxa, 2020)
Tuberocephalus tsengi (Tao, 1963) STAT. REV., an aphid species described from China, is reported feeding on Artemisia vulgaris in southern England. This species is here redescribed and distinguished from T. sasakii (Matsumura, 1917), with which it has previously been synonymised.